The Impact of Regulation on Growth and Informality : Cross-Country Evidence - Loayza, Norman V.; Ovíedo, Ana Maria; Servén, Luis (World Bank, Washington, DC, 2012)
The authors study the effects of regulation on economic growth and the relative size of the informal sector in a large sample of industrial and developing countries. Along with firm dynamics, informality is an important channel through which regulation affects macroeconomic performance and economic growth in particular. The authors conclude that a heavier regulatory burden-particularly in product and labor markets-reduces growth and induces informality. These effects are, however, mitigated as the overall institutional framework improves.